Study on Wireless Network Communication in Stage Hydraulic Monitoring System Based on Internet of Things - Yue Dong; Hui Ren; Jianghui Dong; Liping Wang (Discrete Dynamics in Nature and Society)
A novel stage hydraulic monitoring system based on Internet of Things (IoT) is proposed in this paper. Compared with the traditional wired system, the proposed system is a flexible working method and can save the cost. Furthermore, it has the low power consumption, high safety, and large scale network. The real-time pressure and flow data can be collected by using the nodes in ZigBee network. The fault detection and diagnosis process was used in this study, which was facilitated by measuring pressure of flow. When the monitored data exceeds the normal range, some failure may occur in the stage hydraulic system. If any failure occurs in the circuit, the maintainers can be informed immediately, which can greatly improve maintenance efficiency, ensuring the failure to be eliminated in time. Meanwhile, we can take advantage of wireless sensor network (WSN) to connect the multiple loops and then monitor the loops by using ZigBee technology, which greatly improves the efficiency of monitoring.